(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The development of information technology brings significant transformation in the field of education, especially through the implementation of e-learning. One concrete manifestation of the digitization of learning is the use of Learning Management System (LMS), which serves as an interactive platform for managing, delivering, and evaluating the teaching and learning process. This article aims to examine the development and implementation of LMS in the context of learning, particularly in network communication practices, through a literature study approach. Data is collected from various national and international literature discussing the effectiveness, challenges, and innovations in the use of LMS. The main data source for this research is scientific articles sourced from databases in Google Scholar. The analysis technique used is qualitative content analysis with a descriptive approach. The results of the analysis show that LMS can improve the quality of learning, encourage active participation of students, and provide flexibility in delivering material. The analyzed studies also emphasize the importance of the integration between technical aspects, pedagogical aspects, and user characteristics in designing an effective and adaptive LMS. Thus, the development of interactive project-based and multimedia LMS is highly relevant to support practical learning in network communication in the digital era.